PENYULUHAN TENTANG PEMANFAATAN DIGITAL MARKETING BAGI UMKM DI KABUPATEN SUMEDANG JAWA BARAT - Hasanudin Hasanudin; Dipa Teruna Awaloedin (LPPM Universitas Bina Bangsa, 2023)
MSMEs are believed to be able to boost the Indonesian economy, but the existence of MSMEs using MSMEs are believed to be able to boost the Indonesian economy, but the existence of MSMEs using digital marketing is not matched by a shift in marketing behavior from conventional to digital. The potential for MSMEs to become the center of economic power lies in implementing digital technology-based marketing strategies. MSMEs in Indonesia are expected to be able to choose media for marketing their products through digital media. This is because digital media is the best choice for developing a business, with digital media business actors can reach a wider market both nationally and internationally. Regular specialty media, which require a lot of changes and are much more convoluted, are currently not a major problem for SMEs due to computerized marketing. The reason for this action is to help MSME business people by involving virtual entertainment as their way of progress, etc. Explain the importance of digital marketing in the widespread promotion of their products. Given the intense competition that occurs in the use of digital technology, it is hoped that this activity can motivate business actors. This activity hopes to provide additional knowledge and motivate MSME entrepreneurs to become young entrepreneurs by understanding digital marketing, and with this counseling it is hoped that it can increase motivation, provision and enthusiasm, and we hope that MSME actors are ready to enter the 4.0 era with digital marketing-based in Sumedang and surrounding areas